Patient-specific polymethylmethacrylate prostheses for secondary reconstruction of large calvarial defects: A retrospective feasibility study of a new intraoperative moulding device for cranioplasty. Issue 2 (February 2017) - Moser, Manuel; Schmid, Raphael; Schindel, Ralf; Hildebrandt, Gerhard
Abstract: Purpose: The aim of this study was to review a new template-based technique for intraoperative patient-specific cranioplasty manufacturing (PSCM) with polymethylmethacrylate (PMMA) to cover large calvarial defects. Material and methods: A polypropylene foil thermoformed on a three-dimensional reprint of the calvarial defect was used as an intraoperative moulding device for PMMA between August 2012 and December 2015. Surgical and radiological data were retrospectively reviewed, and a patient questionnaire was used to assess functional and cosmetic outcome (numeric rating scale, Odom's criteria). Results: Seventeen patients (mean age 42.2 ± 14.5 years) received PSCM. Operating time averaged 130 ± 34 min, and the approximate blood loss was 293 ± 185 ml. Volumetric analysis revealed a lower implant volume compared to index bone (mean 66.5 vs. 72 cm 3, p  = 0.513), the mean difference in thickness being the lowest in the posterior parietal and pterional (0.4–0.7 mm) and the highest in the anterior–superior frontal area (1.8 mm). Cosmetic satisfaction averaged 9 ± 1.5, with 70.6% of patients judging the overall result as excellent or good and 29.4% as satisfactory. Mean follow-up was 19.5 ± 13.3 months, with an overall complication rate of 17.6%, including 11.8% surgical site infections (SSIs) and one implant removal. Conclusions: Intraoperative PSCM using PMMA moulded on a thermoformed polypropylene foil leads to satisfactory outcomes. It is a safe technique with complication rates comparable but not superior to those of other alloplastic techniques, but the device has considerable production costs.